Factors related with not receiving rt-PA in patient who arriving within 4.5 hours of Ratchaburi hospital - ทองบัว, สุชาดา; นิลสุข, พลอยชมพู (Hua Hin Medical Journal, 2019)
Objective: To study the factors related with not receiving rt-PA in patient who arriving within 4.5 hours of Ratchaburi hospital, Ratchaburi province. Research design: This is a retrospective study of acute ischemic stroke who arriving in Ratchaburi hospital within 4.5 hours, there were 116 cases between October 1st,2016 – September 30th,2017. The individual data were collected by hospital medical records and analyzed by percentage and chi-square test. Result: This research found that in non-receiving rt-PA patient, there were 11.9 percent of health care provider factor which should not receive rt-PA(P-value < 0.05) and 97 percent of patient and relatives factor who decided to reject rt-PA(P-value<0.05). The other factors, duration of laboratory delivery and computed tomography interpretation time are not related to non-receiving rt-PA in acute (Fast tract) ischemic stroke patient